Model of vulnerability to climate change due to flooding hazard, to calculate the cost avoided. Case Sector El Piste, City of Calca, Cuzco - Montero Chirito, Juan Carlos (2022)
The investigation was based on the theoretical and practical aspects for a model of vulnerability to flooding hazard due to climate change, in order to calculate the avoided cost. It takes as a primary characteristic the variable precipitation. The first step has been an account of the state of the art on modelling vulnerability to flooding in Peru. When it comes to modeling floods, a problem arises that stems abundantly from trying to simulate, with discrete expressions in time and space, a progress that occurs in nature on a progressively much smaller scale. The last stage of the investigation consisted of running the model, this phase compares the numerical results with the control measures to be implemented, outcoming a map of different return periods of flooding impact. The main conclusion is that flood modelling is a function of the study area and meteorological variables. Therefore, reducing the levels of uncertainty remains the main challenge, and even more so if we focus on calculating the cost avoided by floods.